Penggerak Laser portable dengan Bluetooth Berbasis Android - Kurniawan, Benny Danang; , Bana Handaga, S.T.,M.T.,P.h.D (2016)
Most of the use Android devices. Many technological innovations with these devices begin with image manipulation, manipulation camera, control game. More innovation is integrated with Android for a variety of purposes. Laser stands for LASER (Light Amplification by Stimulated Emission of Radiation-Magnification Light by Beam Radiation aroused). Laser has several uses such as: cutting operation, cutting industrial materials, pointing presentation and others. With Android and the laser, the authors aim to make innovation the driving laser beam with Android as controller. The method used in this research was experimental. To control the device using Arduino UNO as the main controller board. Arduino can be in the program using C language tools in the program to run arduino laser buffer corresponding coordinates that have been set and turned on the laser as needed. With the Android device can send commands via Bluetooth to be received by the HC-05 Bluetooth Shield and forwarded to the Arduino. In the pattern pieces tested were straight, "L" shape and Shape "U". The materials used for the test consists of: Iron, wood, plastic mica, plastic bags, cork and black isolation. In addition to the test-piece also do tests on the use of resources. From various experiments, the material of black plastic bags and black insulation that can be cut over 60% of the target. Device controllers are portable laser works best when the electric power source of 9.0 volts at the current 3.0 Ampere